Force-Field Simulations of a Hydrated Lanreotide-Based Derivative: Hydration, Dynamics, and Numerical Evidence of Self-Assembly in Dimers - Pinzan, Florian (ACS Omega, 2020)
[Image: see text] Recently, self-organization of the cyclic octapeptide lanreotide and lanreotide-based derivatives in a nanotube to from a dimer structure has been experimentally evidenced. While the nature of the interactions between both monomers has been strongly investigated no molecular details of the hydration of the monomer and the formation of the dimer have been provided. Using molecular dynamics simulations, this work focuses on the structure, hydration, and dynamics of water and an analog of lanreotide. To do so, several models of monomers based on different schemes of partial charges and electrostatic interaction calculations are considered. By comparison with the experiments, we show that the model based on the combination of the AMBER force-field, CHELPG charge calculation, Ewald sum is the most relevant. Additionally, by mapping the interfacial hydration of the lanreotide monomer we evidence a heterogeneous surface in terms of hydrophilicity involving heterogeneous hydration. Furthermore, we show a slowdown in the translational dynamics of water molecules located close to the lanreotide surface. We also provide the molecular details of the self-assembly in the dimer in terms of structure, hydration, and energy.